Imagining the ‘Tribe’ in Colonial and Post-Independence India - Sanjukta Das Gupta (Ksiegarnia Akademicka Publishing, 2019)
In the context of the changing nature of India’s relationship with her tribal or Adivasi population, this paper seeks to analyse the construction ‘tribes’ in colonial India and how these came to influence contemporary India’s understandings of the category. Arguing that state policies are actuated by myriad ways in which target populations are defined, conceptualized and represented, this paper seeks to trace the contentious categorizations and multiple identities that have been imagined for, thrust upon and assumed by such communities since colonial times. It thus critically explores and engages with a range of ideologies that informed and shaped independent India’s tribal policies.